2014
DOI: 10.1503/cjs.027312
|View full text |Cite
|
Sign up to set email alerts
|

Does ultrasonography accurately diagnose acute cholecystitis? Improving diagnostic accuracy based on a review at a regional hospital

Abstract: Background: Acute cholecystitis is one of the most common diseases requiring emergency surgery. Ultrasonography is an accurate test for cholelithiasis but has a high falsenegative rate for acute cholecystitis. The Murphy sign and laboratory tests performed independently are also not particularly accurate. This study was designed to review the accuracy of ultrasonography for diagnosing acute cholecystitis in a regional hospital. Methods:We studied all emergency cholecystectomies performed over a 1-year period. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
53
1
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(64 citation statements)
references
References 20 publications
5
53
1
5
Order By: Relevance
“…Ultrasonographic imaging examination determines the diagnosis of cholelithiasis with almost 98% sensitivity. Its diagnostic value for AC patients was reported as 54%-90% in the literature [12,13]. Moreover, no correlation has been reported between USI findings and histopathological results for AC [7].…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasonographic imaging examination determines the diagnosis of cholelithiasis with almost 98% sensitivity. Its diagnostic value for AC patients was reported as 54%-90% in the literature [12,13]. Moreover, no correlation has been reported between USI findings and histopathological results for AC [7].…”
Section: Discussionmentioning
confidence: 99%
“…Persistent abdominal pain has 80% sensitivity and 49% specificity (18). Murphy's sign has sensitivity of 68% and specificity of 45%, abdominal tenderness 91% and 20%, respectively (9,18).Temperature > 37.5 C has sensitivity of 3% and 100% specificity, WCC > 9.7 x 10^9/L 64% sensitivity and 47% specificity (9).…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis of AC based on right upper quadrant pain and tenderness, fever, Guidelines (TG07, TG13) and added to existing diagnostic criteria of AC ( Murphy's sign, right upper quadrant mass/pain/tenderness, fever, elevated white cell count , liver ultrasound , magnetic resonance imaging, computed tomography and Tc-HIDA scan) Creactive protein (CRP) (5,6). CRP is not used as a diagnostic bench mark for AC in the United States, Canada, Europe, India, Australia and New Zealand CRP (7)(8)(9)(10)(11). In this setting, reliance on an elevated WCC as a criterion of AC would misdiagnose this condition in neutropenic patients.…”
Section: Introductionmentioning
confidence: 99%
“…8,13,14 In current study, almost 83 % cases of urolithiasis were diagnosed accurately by ultrasound examination of the abdomen as compared to 62 % diagnostic accuracy reported by Haroun AA et al 15 In this study, CECT helped in diagnosis and treatment of 9 patients. Four patients out of 5 suffering from intestinal obstruction were treated surgically and all 5 patients diagnosed as pancreatitis were managed conservatively bases on CECT scan reports.…”
Section: Discussionmentioning
confidence: 49%
“…Similar results have been reported in a study by Hwang H et al which correlates well with observations of the present study. 8 It was also observed that 1 out of 3 patients with acute abdomen was suffering from more serious conditions such as pancreatitis, intestinal obstruction with / without intestinal perforation.…”
Section: Discussionmentioning
confidence: 99%